Credit risk in bank and how to mitigate the risks of Bank Asia Limited - Islam, Rushdi Md. Raihanul (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.